2012
DOI: 10.1016/j.regpep.2011.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fatty acid composition on food intake, triglycerides, and hypothalamic peptides

Abstract: While a high-fat diet when compared to low-fat diet is known to produce overeating and health complications, less is known about the effects produced by fat-rich diets differing in their specific composition of fat. This study examined the effects of a high-fat diet containing relatively high levels of saturated compared to unsaturated fatty acids (HiSat) to a high-fat diet with higher levels of unsaturated fatty acids (USat). A HiSat compared to USat meal caused rats to consume more calories in a subsequent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…Fourthly, the changes in energy intake, especially as fed with high-fat diet, may influence galanin levels in serum and hypothalamus of animals and humans [12,39,103,100,130]. The galanin levels were positive correlated body mass index [9].…”
Section: Effect Of Galanin On Energy Metabolismmentioning
confidence: 97%
See 2 more Smart Citations
“…Fourthly, the changes in energy intake, especially as fed with high-fat diet, may influence galanin levels in serum and hypothalamus of animals and humans [12,39,103,100,130]. The galanin levels were positive correlated body mass index [9].…”
Section: Effect Of Galanin On Energy Metabolismmentioning
confidence: 97%
“…Firstly, administration of galanin or its agonist, galanin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), into paraventricular nucleus (PVN) and central nucleus of the amygdala of animals promoted food intake and weight gain when food was plentiful [29,44,92,100,107,151,183].…”
Section: Effect Of Galanin On Energy Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown rats treated with high fat diets showed increased body fat content and decreased food intake (42,44). It has also been shown the consumption of diets rich in saturated fat reduced the expression of the orexigenic peptides neuropeptide Y (45) and agouti-related protein (46) in the arcuate nucleus of hypothalamus, and increased the secretion of the anorexigenic cholecystokinin (47).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of appetite and stress response [24][25][26] Respiratory effects [27][28][29] Addiction 11,25,26,[30][31][32][33][34][35][36][37][38] Behavioral changes associated with cocaine administration 39 Analgesia 11,40 Food intake regulation 23,41 Central regulation of feeding (of blind cavefish) 42 Regulation of glucose metabolism 43,44 Energy balance regulation 45,46 Insulin secretion regulation 44 Variability in diet-induced obesity sensitivity 47 Proliferation and viability of 3T3-L1 preadipocytes 48 Body temperature regulation 46,49 Neuroendocrine function 6,49,50 Pituitary hormone secretion 51 Cardiovascular activities 49,[52][53][54] Post-ischemic attenuation of inflammatory responses (neuroprotection) 55 Prevention of cerebral ischemic neuronal damage (neuroprotection) 43 Reproduction [56][57]…”
Section: Mechanisms/effects Referencesmentioning
confidence: 99%